Domestic violence role play of a therapy session - Ross, Colins A.; Caldwell, Melissa; Manitou Communications (Texas : Manitou Communications, 2006)
Dr. Ross interview a woman with a history of domestic violence. He plays the role of a worker at a battered women's shelter and Melissa Caldwell, Executive Clinical Director of the Ross Institute, role plays the woman. This is her eight visit to the shelter. The interview illustrates the two core principles of the Trauma Model: the problem of attachment to the perpetrator and the locus of control shift. Dr. Ross explains to the woman why she needs to learn how to tolerate and integrate her ambivalent attachment in order to make healthy decisions about her marriage
Title from title screen
Colin A. Ross, Melissa Caldwell
Keywords: Victims of family violence -- Treatment; Abused women -- Treatment